Rodinný dům - Kožina, Jan (Vysoké učení technické v Brně. Fakulta stavební, 2016)
Předmětem bakalářské práce je návrh rodinného domu. Stavba se nachází ve městě Velká Bíteš na parcele č. 2539/115 o celkové ploše 879,8 m2. Jedná se o dvoupodlažní nepodsklepený objekt, umístěný na mírně rovinatém terénu, přizpůsoben pro bydlení 4 osob. Obvodové stěny domu jsou vyzděny z keramických tvárnic Porotherm a jsou založeny na betonových základových pasech. Stropní konstrukce jsou provedeny ze systému Porotherm z keramických vložek Miako a nosníků POT. Objekt je zastřešen pultovou střechou. Střešní krytina je navržena plechová Lindab Semaline šedé barvy. Schodiště je dvouramenné železobetonové. Součástí objektu je garáž pro 1 automobil.

The subject of this Bachelor's thesis is a design of a residential house. The building is located in the city of Velká Bíteš on plot number 2539/115. The total area is 879,8 m2. This is a two-floors object, without cellar, located on slihty flat terrain, designed for 4 persons. The perimeter walls of the house are lined with clay block from the Porotherm company and they are based on the concrete foundation strips. The ceiling construction are made of Porotherm system of ceramic inlays Miako and beams the POT. The building is designed with shed roof. Roofing is designed of metal LINDAB Seamline grey color. The staircase is a double reinforced concrete. Boot part of the house have a garage for 1 cars.
Residential house
Keywords: Rodinný dům; nepodsklepená budova; základové pasy; tvárnice Porotherm; pultová střecha.; Residential house; building without cellar; foundation strips; clay block Porotherm; shed roof.